SOIL PROPERTIES OF THE EASTERN TOPOSEQUENCE OF MOUNT KELIMUTU, FLORES ISLAND, EAST NUSA TENGGARA AND THEIR POTENTIAL FOR AGRICULTURAL USE - Hikmatullah Hikmatullah; H. Subagyo; B.H. Prasetyo (Indonesian Journal of Agricultural Science, 2003)
Kelimutu stratovolcano is one of the young volcanoes extensively found in Flores island. Studies on volcanic soil properties and their suitability for agricultural development in the whole island are lacking. The research was conducted to evaluate the relationship of elevation and soil properties,  and suitability for agricultural development. Five representative pedons at elevation of 550, 1,000, 1,200, 1,400, and 1,600 m above sea level (asl), respectively, were studied in the field, and 22 soil samples were analyzed in the laboratory. The results indicated that elevation significantly affected soil properties and degree of soil weathering. With decreasing elevation, sand content, amorphous material content, and phosphate retention decreased. Concomitantly, clay content, H2O-pH, exchangeable Ca and Mg, base saturation, and soil-CEC increased. A highly positive correlation was shown between P retention and NaFpH, Al, and (Al+0.5 Fe) contents extracted by acid ammonium oxalate. Soil-CEC also showed significant positive correlation with clay and silt contents, organic carbon, and exchangeable Ca and Mg. Degree of weathering increased with decreasing elevation as reflected by decreasing silt/clay ratio. Soils developed from Entisols (Lithic Udorthents) at 1,600 m asl, to Andisols (Typic Hapludands) at 1,000-1,400 m asl, and Mollisols (Typic Hapludolls) at lower elevation down to 550 m asl. Soils at 1,400-1,600 m asl are unsuitable for  agriculture. Soils at 1,000-1,200 m are moderately suitable for food crops, horticulture, and estate crops. Dominant limiting factors are steep slopes and P retention. Soils at 550 m asl are suitable for food and estate crops, and also lowland horticulture.